Investigating neural responses in models of neurocysticercosis - Tomes, Hayley Sarah (Department of Human Biology, 2021)
Epilepsy is more frequent in sub-Saharan Africa than the rest of the world due to high levels of brain infections by larvae of the pig cestode Taenia solium, a condition termed neurocysticercosis. Despite the large nature of the problem, little is known about how neurocysticercosis modulates neuronal responses to result in the development of seizures. In this thesis I have used the cestode Taenia crassiceps to develop multiple in vitro and in vivo models of neurocysticercosis in rodents. Utilising patch-clamp electrophysiology in organotypic hippocampal brain slices and chronic, wireless electrocorticographic recordings in freely moving animals I have explored how cestode larvae affect neuronal excitability in the brain across a range of time scales. First I demonstrate that homogenate of Taenia crassiceps larvae has a strong, acute excitatory effect on neurons, which is sufficient to trigger seizurelike events. The excitatory component of the homogenate was found to strongly activate glutamate receptors and not acetylcholine receptors nor acid-sensing ion channels. An enzymatic assay showed that the larval homogenate contains high levels of glutamate, explaining its acute excitatory effects on neurons. In the second part of my thesis I demonstrate that longer-term incubation of Taenia crassiceps homogenate with organotypic brain slices over the course of a day does not affect the intrinsic properties of pyramidal neurons nor the excitability of the neuronal network. In the final part of my thesis I established an in vivo model of neurocysticercosis. I found that intradermal inoculation together with multiple intracerebral injections of Taenia crassiceps homogenate did not result in the development of seizures over 3 months of chronic electrocorticography recordings. In addition, the seizure-threshold to picrotoxin, an excitotoxin, was not altered by Taenia crassiceps homogenate injection. Immunohistological analysis of the tissue below the injection site revealed no difference in astrocytes nor the number of microglia. However, microglial processes were observed to be retracted in the Taenia crassiceps group reflecting a moderate neuroinflammatory response. Together the data in my thesis provides novel insight into the acute and chronic effects of Taenia crassiceps homogenate on the excitability of neuronal networks with relevance to our understanding of neurocysticercosis.